Comparison of Dosage of 4mg Versus 8mg Dexamethasone on Post-Operative Swellings in Zygomatic Bone Fractures (Medical Forum Monthly, 2024)
Objective: To compare the mean decrease in swelling with 4mg versus 8mg dexamethasone given preoperatively in patients undergoing surgery for zygomatic bone fractures.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Department of Oral & Maxillofacial Surgery, Saidu Medical College/Saidu Group of Teaching Hospital, Swat KPK from July 2017 to December 2017.Materials and Methods: One hundred patients were included and divided into equal two groups. Group A was given 8mg dexamethasone one hour before surgery while Group B was given 4mg dexamethasone one hour before surgery. Baseline reading of swelling was measured and patients were undergone surgery. Patients were asked to visit after 7 days of surgery in OPD.Results: The mean ages were 27.66±8.38 years in group A and 28.52±8.38 years in group B. There were 82% males and 18% females in group A while in group B, 88% males and 12% females. The mean decrease in swelling, 7.12±3.60 mm in group A while in group B, 5.14±1.84 mm. Statistically the difference was significant (P<0.05) in mean decrease in swelling.Conclusion: The current study concluded that the use of 8mg of the dexamethasone was more effective than 4mg reduce the degree of post operative swelling in zygomatic bone fracture.